Distal Radioulnar Joint Replacement in the Scarred Wrist - Lans, Jonathan; Chen, Shih-Heng; Jupiter, Jesse B.; Scheker, Luis R. (Journal of Wrist Surgery, 2019)
Background Radiocarpal or midcarpal arthritis can occur simultaneously with arthritis of the distal radioulnar joint (DRUJ), leading to functional impairment of the wrist. Treatment often involves wrist arthroplasty or arthrodesis, either with simultaneous or secondary procedures, addressing the DRUJ. Successful treatment of solitary DRUJ arthritis with DRUJ replacement has been reported. However, outcomes in patients with multiple prior wrist surgeries are lacking. Surgery in these wrists is challenging because surgical scarring and advanced bone deformities make implant positioning more difficult. Therefore, the aim of this study was to evaluate the outcomes in patients that underwent total wrist arthrodesis and DRUJ replacement after multiple prior wrist surgeries.Methods We prospectively enrolled patients that underwent total wrist arthrodesis and replacement of the DRUJ, either simultaneously or during separate procedures from 1999 to 2012. We included 14 patients with a median age of 43 years (interquartile range [IQR]: 35–47). As objective outcomes range of motion, weight-bearing ability, grip strength, was measured. For the subjective outcomes, we used an analogue pain score and the disabilities of the arm shoulder and hand (DASH) scores.Results At a median follow-up of 5.6 years (IQR: 3.2–7.1). The average DRUJ range of motion and weight lifting ability significantly improved. As for the subjective evaluations, postoperative pain scores improved significantly, as did the DASH scores. Four of the patients had a postoperative complication, including infection and heterotopic ossification, of which two required reoperations. Additionally, 5 patients developed pisotriquetral arthritis requiring, pisiform excision, triquetrum excision, or the combination of both.Conclusion Distal radioulnar joint replacement with a semiconstrained prosthesis was an effective method to restore the function of the wrist and forearm. As the surgical anatomy and soft tissue envelope were compromised in these patients, additional surgical exposure is necessary, adding to the complexity in these patients. No radiographic looseningLevel of Evidence This is a therapeutic level IV study.
Keywords: distal radioulnar joint arthritis; distal radioulnar joint replacement; midcarpal arthritis; radiocarpal arthritis; wrist arthrodesis